2017
DOI: 10.20944/preprints201703.0094.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Th17 Cells Interactions with the Brain Endothelium in Vitro

Abstract: Abstract:The nature of the interaction between Th17 cells and the blood-brain barrier (BBB) is critical for the development of autoimmune inflammation in the central nervous system (CNS). TNF-α or IL-17 stimulation is known to enhance the adherence of Th17 cells to the brain endothelium. The brain endothelial cells (bEnd.3) express VCAM-1, the receptor responsible for inflammatory cell adhesion, which binds VLA-4 on migrating effector lymphocytes at the early stage of brain inflammation. The present study exam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The above results indicated that propionate and butyrate treatment promoted the recruitment of Th17 cells and CCL20 expression in the lungs. Previous studies reported that several types of cells in the lungs could secret CCL20, for example, endothelial cells, [ 36,37 ] epithelial cells, [ 38,39 ] macrophages, [ 40 ] and tumor cells. [ 41,42 ] To investigate which type of cell secrets CCL20, the endothelial cell line MS1, epithelial cell line MLE12, macrophage cell line Raw264.7, and B16F10 tumor cells were used.…”
Section: Resultsmentioning
confidence: 99%
“…The above results indicated that propionate and butyrate treatment promoted the recruitment of Th17 cells and CCL20 expression in the lungs. Previous studies reported that several types of cells in the lungs could secret CCL20, for example, endothelial cells, [ 36,37 ] epithelial cells, [ 38,39 ] macrophages, [ 40 ] and tumor cells. [ 41,42 ] To investigate which type of cell secrets CCL20, the endothelial cell line MS1, epithelial cell line MLE12, macrophage cell line Raw264.7, and B16F10 tumor cells were used.…”
Section: Resultsmentioning
confidence: 99%
“…However, fairness is perceived in terms of the degree of participation and the opportunity for the parties to express their views rather than the nature of the outcome. 39 People feel more comfortable expressing their concerns and defending their interests in such systems because they know them better and are more familiar with customary rules and values, while they often are often ignorant of the content of statutory law. Interestingly, the Liberia survey points out that femaleheaded households are less likely to agree that customary decisions should prevail over formal ones.…”
Section: Why Engage?mentioning
confidence: 99%